Crosstalk Between the Immune System and Plant-Derived Nanovesicles: A Study of Allergen Transporting - Stanly, Christopher; Kim, Hyoseon; Antonucci, Giuseppe; Fiume, Immacolata; Guescini, Michele; Kim, Kwang Pyo; Ciardiello, Maria Antonietta; Giangrieco, Ivana; Mari, Adriano; Pocsfalvi, Gabriella (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Nanometer-sized membrane surrounded vesicles from different parts of plants including fruits are gaining increasing attention due to their anti-inflammatory and anticancer effects demonstrated by in vitro and in vivo studies, and as nanovectors for molecular delivery of exogenous substances. These nanomaterials are very complex and contain a diverse arsenal of bioactive molecules, such as nucleic acids, proteins, and lipids. Our knowledge about the transport of allergens in vesicles isolated from plant food is limited today. Methods: Here, to investigate the allergenicity of strawberry-derived microvesicles (MVs), nanovesicles (NVs), and subpopulations of NV, we have set up a multidisciplinary approach. The strategy combines proteomics-based protein identification, immunological investigations, bioinformatics, and data mining to gain biological insights useful to evaluate the presence of potential allergens and the immunoglobulin E (IgE) inhibitory activity of vesicle preparations. Results: Immunological test showed that several proteins of strawberry-derived vesicles compete for IgE binding with allergens spotted on the FABER biochip. This includes the known strawberry allergens Fra a 1, Fra a 3, and Fra a 4, but also other IgE-binding proteins not yet described as allergens in this food, like gibberellin-regulated proteins, 2S albumin, pectate lyase, and trypsin inhibitors. Proteomics identified homologous sequences of the three strawberry allergens and their isoforms in total protein extract (TPE) but only Fra a 1 and Fra a 4 in the vesicle samples. Label-free quantitative proteomic analysis revealed no significant enrichment of these proteins in strawberry vesicles with respect to TPE. Conclusion: Immunological tests and bioinformatics analysis of proteomics data sets revealed that MVs and NVs isolated from strawberries can carry functional allergens their isoforms as well proteins potentially allergenic based on their structural features. This should be considered when these new nanomaterials are used for human nutraceutical or biomedical applications.